(untitled) (Eurasian Research Bulletin, 2022)
In this article, the lithological and geomorphological structure of the sandy soils of Central Fergana was studied. Properties and characteristics of sandy soils, genesis, and chemical, agrochemical, physicochemical and ecomeliorative changes occurring in sandy soils under the influence of anthropogenic factors were studied